Digital Transformation Through E-Master Application in Human Resource Development in Civil Servants - Fitriani, kharisma; Hidayat, Rofiq (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2024)
The use of technology has become a crucial aspect in the progress and development of Human Resources (HR). HR management includes various aspects such as planning, organizing, compensation, and maintaining work relationships to achieve individual, organizational, and societal goals. Research in education has a significant impact on youth empowerment, a critical stage in human development. This study aims to describe motivation, personality, and skills in HR Development Management at the East Java Provincial Education Office Branch. Using a qualitative approach, this research understands HR development in depth through the